1999
DOI: 10.2527/1999.7782259x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of virginiamycin on ruminal fermentation in cattle during adaptation to a high concentrate diet and during an induced acidosis.

Abstract: The objective of Exp. 1 was to compare the effects of virginiamycin (VM; 0, 175, or 250 mg x animal(-1) x d(-1)) and monensin/tylosin (MT; 250/ 90 mg x animal(-1) x d(-1)) on ruminal fermentation products and microbial populations in cattle during adaptation to an all-concentrate diet. Four ruminally cannulated, Holstein steers were used in a 4x4 Williams square design with 21-d periods. Steers were stepped up to an all-concentrate diet fed at 2.5% of BW once daily. Ruminal pH, protozoal counts, and NH3-N and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
77
2
24

Year Published

2009
2009
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(124 citation statements)
references
References 26 publications
21
77
2
24
Order By: Relevance
“…The lactate accumulation in the rumen may account for increased acidosis incidence in ruminant animals, reducing the efficiency of energy utilization. Coe et al (1999) observed that virginiamycin is more efficient in controlling lactate production than ionophores. These authors also observed that mean counts of Lactobacillus and Streptococcus bovis, the major lactic acid producing bacteria, were lower for steers receiving virginiamycin than for those supplemented with ionophores.…”
Section: Resultsmentioning
confidence: 89%
“…The lactate accumulation in the rumen may account for increased acidosis incidence in ruminant animals, reducing the efficiency of energy utilization. Coe et al (1999) observed that virginiamycin is more efficient in controlling lactate production than ionophores. These authors also observed that mean counts of Lactobacillus and Streptococcus bovis, the major lactic acid producing bacteria, were lower for steers receiving virginiamycin than for those supplemented with ionophores.…”
Section: Resultsmentioning
confidence: 89%
“…Therefore, conditions that lead to lactate accumulation, such as acute acidosis, should promote proliferation of F. necrophorum. Because lactate accumulation decreases ruminal pH (< 5.5), fusobacterial growth is inhibited (Coe et al, 1999). Despite this, ruminal acidity remains a predisposing factor because the ruminal wall is more likely to permit entry and colonization by F. necrophorum after acid-damage.…”
Section: Fusobacterium Necrophorummentioning
confidence: 99%
“…O aumento de ácido propiônico reduz a energia desperdiçada com a produção de gás, gerando economia de aminoácidos para construção de proteínas. Menor produção de ácido lático e aumento no PH ruminal foram observados por Coe et al, (1999). Ortolan (2010) observou aumento no PH ruminal, aumento na população de protozoários e aumento na taxa de degradabilidade ruminal.…”
Section: Uso De Aditivos Na Alimentação De Ruminantesunclassified